Quantum Theory and its effects on Novel Corona-virus - Dr. Shahzad Aasim (International Journal of Advanced Science and Technology, 2020)
Emerging infectious viral diseases are a major threat to human kind on earth, containing emerging and re-emerging pathogenic physiognomies have raised great public health concern. This study aimed at investigating the global prevalence, biological and clinical characteristics of novel Corona-virus, Wuhan China (2019-nCoV), Severe Acute Respiratory Syndrome Corona-virus (SARS-CoV), and Middle East Respiratory Syndrome Corona-virus (MERS-CoV) infection outbreaks. Currently, novel Corona-virus disease COVID 2019 is already pandemic and causing havoc throughout the world. Scientific community is still struggling to come out with concrete therapeutic measures against this disease and development of its vaccine is far off from sight in immediate near future. However, humanity will be put to such pressures very often in near future and given the present circumstances, what we can expect from the scientific world now? I think QIT (Quantum Information Theory) has answer to this question. One of the very basic mechanisms that every infectious virus follows to infect is the entry of the virus through cell surface receptors, engulfing, un-coating of viral genome and its transcription to form multiple copies and translation to form viral proteins and coating of viral genome to form multiple copies of the viral particles and then of course the cell bursting to infect other cells. This very basic mechanism does not occur randomly but through a regulated and more dynamic process which we may call coding and decoding of information through reduction in error or noise.